Endoscopic Sustainability PrimAry Reporting Essentials (E-SPARE): European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Cunha Neves, João A.; Baddeley, Robin; Pohl, Heiko; Pioche, Mathieu; Lorenzo-Zúñiga, Vicente; Albéniz Arbizu, Eduardo; Mihai Voiosu, Andrei; Römmele, Christoph; Donnelly, Leigh; Elli, Luca; Lopez-Muñoz, Pedro; Henniger, Dorothea; Khalaf, Kareem; Bruno, Marco J.; Arvanitakis, Marianna; Bisschops, Raf; Hassan, Cesare; Messmann, Helmut; Gralnek, Ian Mark; Siersema, Peter D.; Thomas-Gibson, Siwan; Hayee, Bu'Hussain; Rodriguez de Santiago, Enrique; Dinis-Ribeiro, Mário (Endoscopy, 2025)
A growing number of studies aim to evaluate gastrointestinal (GI) endoscopy services from the perspective of their environmental impact. However, there are currently no guidelines or frameworks which provide specifically for the reporting of endoscopy sustainability studies, and a variety of metrics and assessment tools have been employed in the literature. To improve the clarity, transparency, and quality of reporting, the European Society of Gastrointestinal Endoscopy (ESGE) has developed a reporting framework for the community of researchers interested in conducting studies on sustainable GI endoscopy.